Patient reported outcome measures (PROMS) for body image in dermatology: A systematic review - Johannes Kjeldstrup Kristensen; Corina Nielsen; Nora Haloob (Wiley, 2022)
Abstract Introduction It is widely acknowledged that negative body image perception is linked to anxiety, depression, and body dysmorphic disorder. However, there is no gold standard, body image related patient reported outcome measure in use, specific for dermatologic disease, despite evidence to suggest a high prevalence of mental health problems relating to body image in this group of patients. Aim The aim of this study was to perform a review of body image Patient Reported Outcome Measures (PROMs) used in dermatology and to evaluate their effectiveness. Methods Searches were performed in the major databases. Two investigators independently performed full text evaluation by applying an established checklist to evaluate the conceptual model, content validity, reliability, construct validity, scoring and interpretability and respondent burden. Results Six different PROMs were identified of which only one was fully validated. There was a significant lack of patient involvement in the development of PROMs in this context. Conclusions We therefore encourage further research in this field to improve the quality of evidence to better understand the relationship between mental health and dermatologic disease.